Joint application of B. bassiana and M. anisopliae bioinsecticides for controlling rice bugs and improving rice yields - Ponijan; Handayani, Etik Puji; Kurniawati, Nurleni; Rakhmiati; Zulkarnaen (Universitas Lampung, 2023)
The rice bug (Leptocorisa oratorius F.) is a serious pest of head rice (Oryza sativa L.). It feeds on the developing kernels of rice, starting from the heading phase when the panicle is exposed from the boot until the end of the ripening phase, which makes it susceptible to indirect yield loss. Multiple insecticide applications are often made during the hard drought growth stage due to high densities of rice bugs that frequently migrate from nearby harvested fields or as a result of eggs laid by subthreshold populations during the first two weeks of heading. The research was conducted at The Food Crops and Horticulture Laboratory Trimurjo, Central Lampung, from August to October 2020, using a randomized complete block design (RCBD) with 7 bioinsecticide treatments. The objective of the research was to determine the efficacy of integrating biopesticides B. bassiana and M. anisopliae on rice bug mortality and rice yields. The results showed that rice bug mortality increased by 100% with a lethal period of 72 hours after exposure to B. bassiana 5 g L-1 + M. anisopliae 5 g L-1. Additionally, there was a 19.73% increase in the percentage of rice grain maturity (hard dough) and a reduction of 99.4% in damage (empty grain) compared to the control.